O PROBLEMA DO MAL BANAL E AS SUAS NOVAS MANIFESTAÇÕES NO ENSINO DE HUMANIDADES E O COMPROMISSO ÉTICO-POLÍTICO DA EDUCAÇÃO APÓS AUSCHWITZ - Zanardi, Isis Moraes (2018)
This paper discusses the importance of the teaching of Humanities and the implications of its abandonment, as an occurrence of new manifestations of atrocities. This is to show that the emptying of interest in teaching Humanities could affect the basic structure of the democratic society and the Constitution of a critical-reflective and ethical citizen-politician as well as culminating in an empty process of thought and inability to take responsibility for their actions. To do such, the methodology began in a review of the main works of Hannah Arendt (1906-1965) and other authors who address such issues. In order to analyze the gathered data, it was used as Laurence Bardin’s content analysis (2016) which aims to analyze data through a quali-quantitative method and later producing inferences about what is being analyzed, with the possibility of questioning and verifying wheter the data collected indicate what it proposes to investigate, that is, if the textbooks provided by the national plan of the Textbook (PNLD) are able, as educational support, to discuss the ciziten formation concepts and the human person in the disciplines of Philosophy, Sociology and History. This dissertation is organized from a theoretical framework upon the human formation, the inability of thinking and the teaching of Humanities. Initially, it examines the theme of human formation in relation to the inability of thinking, making considerations about the problem of evil in according to Hannah Arendt. From the analysis of the Origins of Totalitarianism, from 1951, and Eichmann in Jerusalem: a report on the banality of evil, from 1963, it is intended to reflect the mechanisms that produce numbness in the ability of thinking regarding the need of the human formation. With such analysis, it can be perceived that the problem of evil takes not only a radical bias, but also a possibility of a complete destruction of the human, caused by the inability to put oneself in the place of the Other, hence not seeing it as a means in itself, but only means to an end, that is, such problem transforms the human being in a superfluous one. The analysis Eichmann’s case, Arendt realized that the defendant acted banally, manifesting his inability to think, therefore, making possible the normalization of insensibility towards the different. The banality of evil implies the inability to think, a continuous threat to the human formation. The analysis of the textbooks were intended to introduce the discussion concerning the support given to students that while checking, were flawed when it comes to building the human being, as a being who needs and deserves a reflexive training, with the aim of avoiding the trivialization of evil, i.e., empty of thought and the inability to think and judge. Finally, moving towards the final considerations related to education as a process of formation in the political dimension, it is about transforming information in knowledge, and knowledge in wisdom so there won't be any noises in the formation of the integrity of the ethical-political commitment in the shaping of future citizens.